Assessing health workers' performance : a manual for training and supervision - Katz, F. M. (Frederick Manfred), 1923-; Snow, Richard E., 1936-1997 (Geneva : World Health Organization ; [Albany, N.Y. : Sold by WHO Publications Centre USA], 1980)
Hoe pak je de verzorging van een patiënt(e) aan, wat doe je eerst, wat zijn de belangrijkste aandachtspunten, ... ???
Keywords: Medical personnel -- Rating of -- Forms; Medical personnel -- Rating of; Medicine -- Ability testing -- Forms; Medicine -- Ability testing; Blank forms